STRATEGI PEMBELAJARAN KOOPERATIF BERBASIS KONSTRUKTIVISME UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PKN DI SEKOLAH DASAR - Apit Dulyapit; Sita Husnul Khotimah; Tiara Nanda (STAI ALHIKMAH Jakarta, 2024)
AbstractThis article aims to determine the learning outcomes of class II students at SD IX Pengasinan, Bekasi City, in civic education on mutual cooperation. The study employs a constructivism-based cooperative learning approach to evaluate its effectiveness in enhancing student knowledge. Conducted as classroom action research (PTK) with 26 students, the methodology includes planning, action, observation, and reflection stages. The results indicate a significant improvement in student scores, classified as